Deconstructing Hybrid Work: Technostress, Cognitive Permeability, And The Urgency Of E-Leadership - I Dewa Gede Sayang Adi Yadnya; A. Sobandi A. Sobandi; Agus Rahayu; Lili Adi Wibowo; Yeni Fajrin (JURNAL ECONOMINA, 2026)
The radical transformation toward hybrid work models post-pandemic has redefined organizational boundaries while simultaneously triggering technostress, which threatens employee well-being. This study aims to map the drivers, impacts, and mitigation strategies of technology-induced stress in hybrid work environments through a scoping review approach. Following the PRISMA-ScR protocol, 50 peer-reviewed articles (2020-2025) were synthesized from the Scopus database. Findings indicate that the primary antecedents of technostress are rooted in techno-invasion, the "always-on" culture, and information overload, which trigger unique psychophysiological strains such as videoconferencing fatigue. This study offers theoretical novelty by reconceptualizing the Job Demands-Resources (JD-R) model, positioning technology as a paradoxical entity acting as both a resource and a stressor. The synthesis emphasizes the critical role of virtual leadership (E-Leadership) and "Right to Disconnect" policies as primary buffers in mitigating the negative impacts of digitalization. The study concludes that organizational sustainability in the hybrid era depends on a managerial paradigm shift from presence-based monitoring to the protection of employees' cognitive energy capacity.